TIME OF TRANSITION IN UZBEKISTAN AND THE CONCEPT OF PERSONALITY - Sadullo Dilmurodovich Kuronov (Journals Park Publishing, 2023)
In the article, the novels "Dinosaur", "Equilibrium", "Bazaar" are analyzed on the basis of the category of the concept of man. It is proved that the writers systematized the philosophical, economic and social factors of the citizen of capitalism and created a new concept of man. It is proved that in these novels for the first time the figure of Homo Economicus is conceptually described, based on the economic and philosophical views of Adam Smith.
Keywords: human conception, artistic conception, novel thinking, Uzbek novels, economic man, social man, transitional period.